Transformasi Pembelajaran Al-Quran: Studi Fenomenologi Peralihan Metode Ummi ke Utsmani di Taman Pendidikan Al-Qur’an Khairunnas Bandar Lampung - Addzaky, Khoirul Umam; Alfani, Ilzam Hubby Dzikrillah (MASALIQ, 2024)
The transformation of Al-Quran learning methods from Ummi to Uthmani in Al-Quran education institutions is an interesting phenomenon to study, given the complexity of the change process involving various learning components. This study aims to explore the dynamics of the change in Quranic learning methods and analyze its impact on various aspects of learning at the Khairunnas Qur'anic Education Park in Bandar Lampung. Using a qualitative approach with a case study method, this research involved in-depth interviews with teachers, managers, and student guardians, participatory observation of the learning process, and documentation analysis during the transition period. The results show that the learning method transformation process involves three main stages: preparation through intensive training, gradual implementation with a mentoring system, and continuous evaluation. Significant challenges faced include resistance to change, the need to adjust teachers' competencies, and the reorganization of the learning system. The impact of the transformation is seen in changes in the pattern of teacher-student interaction that is more interactive, modification of learning media that is more comprehensive, and development of a more holistic evaluation system. This research contributes to the development of a transformation model of Al-Quran learning methods that can be a reference for similar institutions. The research findings highlight the importance of a systematic approach in managing changes in learning methods, as well as emphasizing the need for continuous professional development in the context of Qur'anic education.